2011
DOI: 10.1002/mar.20404
|View full text |Cite
|
Sign up to set email alerts
|

Retail therapy: A strategic effort to improve mood

Abstract: International audience"Retail therapy" is often applied to the notion of trying to cheer oneself up through the purchase of self-treats. The negative moods that lead to retail therapy, however, have also been associated with greater impulsivity and a lack of behavioral control. Does this lead to mindless shopping when consumers are "down" and regret later? The current work documents that a bad mood does lead to greater purchase and consumption of unplanned treats for the self. However, it also provides evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(150 citation statements)
references
References 42 publications
7
141
1
1
Order By: Relevance
“…The current research acknowledges that the tendency to impulse buy may be influenced by hedonistic character traits of the online consumer [33] as well as forming a kind of 'retail therapy' [5]. Nevertheless, a snapshot of the research participants found the following: most online purchases appear to be planned (62.5%), whereas around 26% are unplanned (see figure 6).…”
Section: Impulse Buying and Purchase Promptsmentioning
confidence: 80%
“…The current research acknowledges that the tendency to impulse buy may be influenced by hedonistic character traits of the online consumer [33] as well as forming a kind of 'retail therapy' [5]. Nevertheless, a snapshot of the research participants found the following: most online purchases appear to be planned (62.5%), whereas around 26% are unplanned (see figure 6).…”
Section: Impulse Buying and Purchase Promptsmentioning
confidence: 80%
“…Some scholars proposed that the reason leading to sad-spending is not because consumption could transfer peoples' focus, but due to the feeling of losing control (Atalay & Meloy, 2011). They found that increasing participants' sense of control would decrease sad-spending (Lerner & Garg, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies only examined that sadness would lead to more consumption behavior, but rarely examined the impact of sad-spending on emotional recovery process. Atalay (2011) found that sad participants would consume more and their emotions were improved after compensation consumption (Atalay & Meloy, 2011). Scott (2012) also discovered that, sad participants' emotions turned better after finishing consuming tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research characterizes retail therapy as purchases of small indulgences strategically acquired to repair moods (Atalay & Meloy, 2011). Regulation of moods, most often up-regulating bad moods, helps individuals manage their emotions so that their internal affective states are relatively stable (Carver & Scheier, 2003).…”
Section: Emotion Repairmentioning
confidence: 99%